Promoting education under distortionary taxation: Equality of opportunity versus welfarism - Pertti Haaparanta; Ravi Kanbur; Tuuli Paukkeri; Jukka Pirttilä; Matti Tuomala (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
How does the public provision of education and the deployment of distortionary tax and subsidy instruments differ when the government's objective is conventional welfarist compared to when the objective is the non-welfarist one of equality of opportunity? This paper develops a framework in which the tax and provision rules in the two settings can be easily compared and contrasted. A range of results are derived which help to answer questions such as whether it is the case that progressive taxation is not used at all under opportunities-based objectives. We show that progressive taxation still plays a role in achieving the objective of equal opportunities, and illustrate how its use may differ under the two objectives. We also show how the provision of public education depends on how private education choices respond, especially the differential responses by higher- and lower-income families. These themes reflect concerns in the policy discourse, and our framework provides an entry point into a systematic exploration of a broad range of issues in comparing the consequences of welfarist and equality of opportunity objectives.
Keywords: H21; H40; O12; 330; educational subsidies; equality of opportunity; income taxation; inequality; public good provision